The effect of thermocycling on the microleakage of a mixture of copper oxide nanoparticles and flowable composite: In-vitro study - Alireza Daneshkazemi; Abdolrahim Davari; Zahra Usefi; Niloofar Fallah; Solmaz Ghanbarnejad; Pedram Daneshkazemi (Tehran University of Medical Sciences, 2021)
Background and Aims: Adding nanoparticles to dental composite resins, could reduce bacterial adhesion and secondary caries. Thermocycling can resemble in-vitro conditions to the oral environment. The aim of this study was to determine the effect of thermocycling on the microleakage of a mixture of copper oxide nanoparticles and flowable composite. Materials and Methods: In this in-vitro study, 88 premolar teeth were divided into eight groups based on the application of copper oxide nanoparticles with concentrations of 0.1% and 0.3% w/w and thermocycling by 0, 1000, 5000 and 15,000 cycles. The occlusal grooves of the teeth were sealed with the mixture of flowable composite and copper oxide nanoparticles, and the teeth were thermocycled. Next, the teeth were immersed in methylene blue 2% solution for 24 hrs and were cut and the microleakage was evaluated by a stereomicroscope (hp/USA). Data were analyzed using Kruskal-Wallis and Mann-Whitney tests at the significance level of 0.05. Results: In the groups with 0.1 % copper oxide nanoparticles, the mean microleakage increased significantly with increasing the number of thermocycling rounds (P=0.032). The difference in the microleakage between the groups exposed to 0 and 15,000 termocycling was significant (P=0.019). However, thermocycling had no significant effect on the microleakage of groups with concentration of 0.3% (P=0.780). The specimens subjected to the 0, 1000, 5000 and 15000 thermocycling in two concentrations of copper oxide nanoparticles showed no significant difference in the microleakage. Conclusion: In groups containing copper oxide nanoparticles with a concentration of 0.1%, the microleakage increased by increasing the number of thermocycling up to 15,000 cycles compared to the control group. However, this did not have significant effect for the concentration of 0.3% copper oxide nanoparticles.